Respuesta :

-------------------------------------------------------------
Equation
-------------------------------------------------------------
m + n² 

-------------------------------------------------------------
Substitute value of m and n into the equation
-------------------------------------------------------------
When m = 2, n = -2
m + n² = 2 + (-2)²
m + n² = 2 + 4
m + n² = 6

-------------------------------------------------------------
Answer : 6
-------------------------------------------------------------
ACCESS MORE